Functional Erosion of Law and the Genesis of Moral Vacuum: An Analysis of Causality in Aquinas' Lex Naturalis Perspective on Threats to Civilization (Contrarius Series: Law & Social Justice, 2026)
This article discusses the functional erosion of law, which has shifted from being a protector of justice (regula iuris) to an instrument of power (instrumentum regni) through rigid formalism. This dysfunction erodes substantive justice, creates a moral vacuum in society, and results in ethical degradation, weakened communal responsibility, and a loss of public trust. This article uses normative legal research, specifically tracing the direct causal relationship between the weakening of legal effectiveness and public moral decay, a correlation that is rarely discussed comprehensively in the literature. Through a deconstruction of the crisis of legal legitimacy within the framework of Thomas Aquinas, this article identifies that contemporary legal problems stem from the disconnection of lex humana (positive law) from lex naturalis (natural law) and lex aeterna (eternal law). Law that ignores Aquinas' morality is degraded into lex iniusta (unjust law), losing its validity and moral binding force. The novelty of this article lies in its systematic emphasis on the causal mechanism between the loss of the instrumental power of law and the moral collapse of society. As a solution, this article emphasizes the urgency of restoring the teleological function of law as a guardian of morality and a pillar of civilization. This requires the re-integration of the principle of lex naturalis into the substance and implementation of positive law, making law a moral orthodoxy based on substantive justice and bonum commune. Implementation strategies include the internalization of morality in legislation, the strengthening of legal ethics education, the reconstitution of the legitimacy of legal institutions through accountability and transparency, and the stimulation of morality-based public participation. The revitalization of lex humana as a guardian of morality is a philosophical and practical imperative, requiring collective synergy to revive the moral consciousness of society so that the law authentically reflects universal justice